2010
DOI: 10.1017/s0317167100010520
|View full text |Cite
|
Sign up to set email alerts
|

Selective 4 Vessels Angiography in Brain Death: A Retrospective Study

Abstract: 492In Canada, neurologic determination of death (NDD) or brain death (BD) diagnosis is based on five clinicals criteria: established etiology capable of causing NDD, deep unresponsive coma, absent brainstem reflexes, absent breathing reflex and absent confounding factors. 1 However, ancillary tests are sometimes necessary when the clinical exam cannot be completely performed or when confounding factors are present. Recently, a Canadian workforce of experts in brain death and organ donation published guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…This phenomenon is commonly observed in angiographic studies. Munari et al reported stasis filling in 5 % (one out of 20), Braun et al in 11 % (15/140), Bradac et al in 12.5 % (two out of 16), Kricheff et al in 15 % (three out of 20), and Savard et al in 28 % (nine out of 32) of cases [2, 69]. CTA studies reveal even higher prevalence of intracranial filling.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is commonly observed in angiographic studies. Munari et al reported stasis filling in 5 % (one out of 20), Braun et al in 11 % (15/140), Bradac et al in 12.5 % (two out of 16), Kricheff et al in 15 % (three out of 20), and Savard et al in 28 % (nine out of 32) of cases [2, 69]. CTA studies reveal even higher prevalence of intracranial filling.…”
Section: Discussionmentioning
confidence: 99%
“…21 Inability to perform an apnea test is uncommon in some series of consecutive patients, but existing data, all from single centers, are somewhat conflicting. 22,23 Differences between centers can likely be explained by multiple factors, including patient characteristics within a particular intensive care unit, typical time lags before patients are assessed for brain death, and individual physician preferences. The degree of hypoxemia and the presence of metabolic acidosis are recognized predictors of inability to complete an apnea test.…”
mentioning
confidence: 99%
“…These spinal responses include brief, slow movements in the upper limbs, flexion in the fingers, fine finger tremors, 17 or arm lifting; and they do not become integrated into truly coordinated decerebrate or decorticate responses. [18][19][20][21][22] They extinguish with repeated stimulation. Ocular "micro tremors" and eyelid opening have been incidentally noted.…”
Section: Absence Of Motor Response To Noxious Stimuli In All Limbsmentioning
confidence: 99%